Definitive proof of graphene hydrogenation by Clemmensen reduction: use of deuterium labeling1. Issue 23 (21st June 2015) - Sofer, Zdeněk; Jankovský, Ondřej; Libánská, Alena; Šimek, Petr; Nováček, Michal; Sedmidubský, David; Macková, Anna; Mikšová, Romana; Pumera, Martin
<x xml:space="preserve">Abstract</x> Clemmensen reduction is efficient method for synthesis of partially hydrogenated graphene.